BEL UMURTQALARI DISK CHURRALARI QAYTALANISHI PROFILAKTIK JIHATLARI - Mamajanov B.S, Qodirov D.R (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
This article is devoted to the study of preventive approaches aimed at preventing the recurrence of lumbar disc herniation, in particular, the effectiveness of traction methods. Lumbar hernia recurrence causes a decrease in the quality of life of patients with neurological and spinal diseases. Traction therapy is a treatment that stretches the spine and reduces pressure on the spinal discs while preventing the recurrence of a herniated disc. In the article, the preventive aspects of traction methods and the effect on the rehabilitation process of patients are analyzed based on the clinical observations made in 2023-2024 in the neurosurgery department of the Mubinakhon-shifo OK clinic. The article also shows the possibilities of reducing the risk of hernia recurrence using traction procedures and evaluates their effectiveness.